PENGARUH CITRA MEREK, KUALITAS PRODUK DAN ULASAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN SKINCARE GLAD2GLOW DI KOTA BATAM - Dorkas Surya Ningsih Zebua; Hikmah Hikmah (LPPM Universitas Putera Batam, 2025)
This research aims to examine the influence of brand image, product quality and product reviews on purchasing decisions for Glad2Glow Skincare in Batam City. This study uses a quantitative research method. The research sample consisted of 204 respondents who were people who had purchased and used Glad2Glow Skincare in Batam City. The data collection method used was primary data. Data processing used the SPSS Version 29 program. Based on the data and analysis that have been carried out, this study shows that brand image positively and significantly influences purchasing decisions for Glad2Glow Skincare in Batam City. In addition, product quality positively and significantly influences purchasing decisions for Glad2Glow Skincare in Batam City. Product reviews positively and significantly influence purchasing decisions for Glad2Glow Skincare in Batam City. And simultaneously, brand image, product quality and product reviews positively and significantly influence purchasing decisions for Glad2Glow Skincare in Batam City.